Hutan Mangrove Petengoran, Pesawaran: Kajian Ekologi Dan Etnosentris - Rahmadini, Adinda; Suciani, Tanti; Fitriani, Aisyah; Fauziah, Firza; Turriza, Zahra; Yudiyanto, Yudiyanto; Wakhidah, Anisatu Z. (Universitas Muhammadiyah Prof. Dr. Hamka, 2024)
Background: Mangrove environments play an essential function in coastal tidal areas. Petengoran mangrove forest is located in Gebang village, Teluk Pandan district, Pesawaran, Lampung province. Describe the ecological and ethnocentric conditions of the Petengora mangrove forest in Gebang village, linked to mangrove vegetation to facilitate forest maintenance, community empowerment, and community impacts on Petengoran mangroves. Methods: This research uses the transect method at three stations with four plots. Each plot had an area of 10 x 10 m2. Ethnocentric data collection was conducted using questionnaires and field observations. Results: INP of Rhizopora mucronata was the highest (300%). The station's overall diversity level (H') is medium. The specific richness index (R) of all stations is low. All stations' uniformity index (E) is high, as shown by findings from community interviews on ethnocentric elements of Petengoran mangrove ecotourism. The environmental conditions of the mangrove forests are relatively clean and maintained, and the infrastructure and ecotourism infrastructure are pretty adequate. Conclusions: Petengora mangroves are managed by farmers who create nurseries and plantations. This area is a mangrove reserve. The mangrove forest is considered a traditional place, but surrounding communities do not have any unique traditions.